Залізні речі черняхівської культури з Музею археології та етнографії Слобідської України - Любичев, М.В.; Скирда, В.В.; Усанов, С.А. (Археологія, 2004)
До наукового обігу введено нові черняхівські речі, що є ще одним внеском у вивчення господарства та військової справи цієї культурної спільності. В публикации в научный оборот вводятся железные наральник и боевой топор из фондов музея. Они обнаружены соответственно на поселениях близ Коломака и Изюма (Оболонь 5). До этого в ареале Черняховской культуры было известно 24 находки боевых топоров и 39 находок наральников. Железные наральники до сих пор не были известны на Черняховских памятниках Днепровского Левобережья. This publication is devoted to iron ploughshare and axe head from the collection of the Karazin National University Museum in Kharkiv, The objects were discovered on the settlements near Kolomak and lzyum (Obolon-5) respectively. Prior to this find. 24 iron axe heads and 39 ploughshares have been associated with the Cherniakhov culture by scholars. Iron ploughshares have never occurred on the Cherniakhov sites of the DnipcUs left bank before.